Satisfacción laboral en egresados de Odontología de universidades de la ciudad de Iquitos, 2024 - Flores Torres, Augusta Elina (2024)
The objective of this research study was to compare the level of job satisfaction among Dentistry graduates from universities in the city of Iquitos in the year 2024. A cross-sectional, descriptive, observational study and a non experimental design was carried out.. The population under study was composed of 444 professionals who graduated from the Dentistry career, to whom a survey (General Job Satisfaction Scale) was applied to collect the necessary information. The results obtained allowed us to conclude that the majority of dentistry graduates in Iquitos express a high level of job satisfaction (48.4%), followed by 33.8% with medium satisfaction and 17.8% with low. UNAP stands out in high satisfaction, UPO in medium, and UCP presents a balance between the categories. Regarding intrinsic factors, 45.3% perceive high levels, 36.9% medium and 17.8% low, with UNAP standing out in high and low factors, and UPO in medium. Regarding extrinsic factors, 51.1% report high satisfaction, 30.6% medium and 18.2% low, with UNAP standing out in high and medium, and UPO in high.